The role of endosarcomeric cytoskeleton proteins in the mechanisms of left ventricular diastolic dysfunction: focus on titin - V. V. Kalyuzhin; A. T. Teplyakov; I. D. Bespalova; E. V. Kalyuzhina; G. E. Chernogoryuk; N. N. Terentyeva; E. V. Grakova; K. V. Kopeva; V. Yu. Usov; N. P. Garganeeva; I. K. Livshits; I. V. Petrova; et al. (Бюллетень сибирской медицины, 2023)
Recognizing the fact that isolated left ventricular (LV) diastolic dysfunction (DD) underlies approximately 50% of all heart failure cases requires a deep understanding of its principal mechanisms so that effective diagnostic and treatment strategies can be developed. Despite abundance of knowledge about the mechanisms underlying DD, many important questions regarding the pathophysiology of diastole remain unresolved. In particular, the role of endosarcomeric cytoskeleton pathology in the deterioration of the so-called active (relaxation of the LV myocardium and the atrioventricular pressure gradient at the beginning of diastole, closely related to it in a healthy heart) and passive (myocardial stiffness) characteristics of diastole needs to be clarified.The lecture briefly discusses the complex hierarchy of DD mechanisms (from the sarcomere to the whole heart) and covers the role of the giant protein titin in the latter, which is the main determinant of intracellular stiffness. Impairment of myocardial relaxation and deterioration of its wall compliance under a wide range of pathological conditions (pressure overload, ischemia, inflammation, cardiotoxic effects, oxidative stress, etc.) underlying DD can be explained by a shift in titin expression toward its more rigid N2B isoform, hypophosphorylation by protein kinases A and G or dephosphorylation by serine / threonine phosphatase 5 of its molecule in the extensible protein segment containing a unique N2B sequence, hyperphosphorylation of PEVK regions of titin by protein kinase C, as well as inhibition of the Ca2+-dependent titin – actin interaction.The results of deciphering these mechanisms can become a tool for developing new approaches to targeted therapy for diastolic heart failure that currently does not have effective treatment, on the one hand, and the key to understanding the therapeutic effects of drugs already used to treat chronic heart failure with preserved LV ejection fraction, on the other hand.